Karaim’s traditions and educational aspirations in the 19th/20th century (outline of the problem) - Wróblewska, Urszula (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
Karaite families cultivated their ancestors’ traditions and the love of learning was passed onto subsequent generations. Family, as an original and closest educational environment that inculcated religious values into a child and taught them their mother tongue, was the source of shaping Karaim attitudes. Despite the importance of family environment, the upbringing depended mostly on financial situation and social status of a family. In Karaite municipalities in the 19th/20th century there were traditional religious schools called midrash functioning next to kenesas (houses of prayer). Teachers who taught religious rules and practises, and Karaite language, played an important role in passing religious knowledge.
Keywords: Karaites; traditions; upbringing; education; family; teachers